Treatment of Autistic Spectrum Disorder - Cerrato Huayaney, Jessica K. (2021)
Early and comprehensive intervention for Autism Spectrum Disorder with behavioral programs Lovaas or Denver as well as cognitive behavioral therapy, training in social skills, sensorineural therapy and speech therapy are essential for a better evolution and prognosis of the main symptoms presented by children and adolescents who suffer from this condition, although there is still no definitive evidence of improvement of these symptoms with drugs, the use of these is postponed for the treatment of comorbidities such as attention deficit disorder, anxiety disorder, depression, etc., may present in the course of this disorder.